Atomic structure and formation of CuZrAl bulk metallic glasses and composites. (November 2015) - Kaban, I.; Jóvári, P.; Escher, B.; Tran, D.T.; Svensson, G.; Webb, M.A.; Regier, T.Z.; Kokotin, V.; Beuneu, B.; Gemming, T.; Eckert, J.
Graphical abstract: Partial radial distribution functions for Cu47.5 Zr47.5 Al5 metallic glass and relevant crystal structures. Abstract: Cu47.5 Zr47.5 Al5 metallic glass is studied experimentally by high-energy X-ray diffraction, neutron diffraction with isotopic substitution, electron diffraction and X-ray absorption spectroscopy. The atomic structure of the glass is modeled by reverse Monte-Carlo and molecular dynamics simulations. RMC modeling of seven experimental datasets enabled reliable separation of all partial pair distribution functions for Cu47.5 Zr47.5 Al5 metallic glass. A peculiar structural feature of the ternary alloy is formation of the strong Al–Zr bonds, which are supposed to determine its high viscosity and enhanced bulk glass formation. Analysis of the local atomic order in Cu47.5 Zr47.5 Al5 glass and Cu10 Zr7, CuZr2 and CuZr B2 crystalline structures elucidates their similarities and differences explaining the phase formation sequence by devitrification of the glass.